Baktiseraga Village Governance as a Best Practice of Good Governance in Buleleng Regency - Yudha Pratama, Kadek Dwinda; Rahmawati, Putu Indah; Heryanda, Komang Krisna (Dinasti Publisher, 2026)
This study aims to comprehensively explore the implementation of good governance principles and identify the enablers and barriers of governance capacity in Baktiseraga Village, Buleleng Regency. Amidst the widespread phenomenon of village fund misallocation at the local level, Baktiseraga Village emerges as a high-performing entity that warrants deep investigation. By integrating Stakeholder Theory to analyze the Pentahelix actors and the Governance Capacity Framework (GCF) for systemic dimensions, this qualitative study employs an in-depth case study design. Data were gathered through semi-structured interviews with 15 key informants, non-participant observations, and documentation studies, which were then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The GCF scoring results demonstrate that Baktiseraga Village has successfully achieved a highly optimal transformative capacity level (score ++) in granular information transparency, inclusive accountability, and organic public participation with zero transaction costs by revitalizing the cultural value of ngayah. However, administrative gaps in formal authority and the institutionalization of innovation that remains person-centric pose potential barriers. This study concludes that the governance model of Baktiseraga Village represents a valid best practice in local public administration, offering a strategic recommendation to codify these innovations into Village Regulations.